Study of clavicle : length and curvatures in South Indian population - R Sudha (Wolters Kluwer Medknow Publications, 2014)
Background and aim of the study: The clavicle is a subcutaneous bone most frequently fractured at the junction of its lateral and middle third of the shaft. Anatomical variations of the curvatures of clavicle can be of relevance for surgical correction procedures like intramedullary or internal plate fixation. The aim of the present study was to observe variations of length and medial and lateral angles of curvatures of the clavicle in a sample of South Indian population. Materials and methods: One hundred and thirteen unpaired clavicles(50 left side,63 right side) of unknown sex and age were studied from the bone collection available at Anatomy departments of Annapoorana Medical College, Vinayaka Mission's Medical and Homeopathy Colleges, Salem. To measure the angles, Parsons method and a protractor was used. Length of the clavicle was measured with a Vernier Calipers. Observation: The average length of the clavicle was found to be 13.74cm left side and 13.76cm on the right side.The average medial angle of the clavicle on the left side is 146° and right side is147.5° .The average lateral angle on the left side is 144° and right side is 142.05°.The total average angle of the clavicle is 290.30° on left side and 289.59° on right side. Conclusion : The average length of the clavicle on the right side is more than the left side.The medial angle on the right side and the lateral angle on left side are more than corresponding opposite sides. These variations can be useful for the orthopaedic surgeons during the surgical correction procedures of clavicle fractures.